2011
DOI: 10.1007/s00422-011-0464-4
|View full text |Cite
|
Sign up to set email alerts
|

Robust control of CPG-based 3D neuromusculoskeletal walking model

Abstract: This paper proposes a method for enhancing the robustness of the central pattern generator (CPG)-based three-dimensional (3D) neuromusculoskeletal walking controller. The CPG has been successfully applied to walking controllers and controllers for walking robots. However, the robustness of walking motion with the CPG-based controller is not sufficient, especially when subjected to external forces or environmental variations. To achieve a realistic and stable walking motion of the controller, we propose the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Some examples of these include the λ-model [44], the central pattern generator [29], [35], [47], and Lie group symmetry [42]. These approaches can generate adaptive motion for unpredictable environments without effecting the system stability.…”
Section: B Motor Control In Biological Systemsmentioning
confidence: 99%
“…Some examples of these include the λ-model [44], the central pattern generator [29], [35], [47], and Lie group symmetry [42]. These approaches can generate adaptive motion for unpredictable environments without effecting the system stability.…”
Section: B Motor Control In Biological Systemsmentioning
confidence: 99%
“…Specifically for human locomotion, several walking experiments have been conducted that report on the immediate responses of the human spinal control to different types of unexpected disturbances including electrical stimulation (Simonsen and Dyhre-Poulsen, 1999; Courtine et al, 2007), mechanical perturbation at individual leg joints (Dietz et al, 1990; Sinkjaer et al, 1996; Faist et al, 1999), and more natural mechanical perturbation of the whole body (Schillings et al, 1999; Sloot et al, 2015). Although external disturbances have been used in neuromechanical human walking models to either test the robustness of control models (Aoi et al, 2010; Kim et al, 2011; Song and Geyer, 2015a) or to study specific high-level recovery strategies (Jo, 2007; Murai and Yamane, 2011), comparisons of the reference data on the reactions of the human spinal control to the reactions predicted by the different walking models have so far not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many researchers resort to forward dynamic simulations of the human neuromuscular system to propose and test different controller architectures [1]- [6]. These studies have demonstrated that different architectures can generate walking or running behaviors with more or less humanlike kinematics, kinetics and muscle activation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated that different architectures can generate walking or running behaviors with more or less humanlike kinematics, kinetics and muscle activation patterns. Examples include models proposed based on the observation of central pattern generators (CPG) in neurophysiological studies [1]- [3], [6], [7]; on the equilibrium point hypothesis [4], [8]; and on muscle reflexes [5], [9]. However, among all the different models, only a few based on CPG control have been generalized to three-dimensional locomotion [3], which limits the ability to study and compare alternative neural controllers of 3D-related motions (including for instance body yaw and roll, and turning).…”
Section: Introductionmentioning
confidence: 99%